Transportation and traffic theory in the 21st century proceedings of the 15th International Symposium on Transportation and Traffic Theory, Adelaide, Australia, 16-18 July 2002 - Taylor, M. A. P. (Emerald, 2002)
This volume contains the formal proceedings of the 15th International Symposium on Transportation and Traffic Theory (ISTTT), which was held at the University of South Australia in Adelaide, Australia on 16-18 July 2002. The ISTTT series is the peak gathering for the world's transportation and traffic theorists. It deals exclusively with the scientific aspects of transportation and traffic phenomena. Although it embraces a wide range of specific topics, from traffic flow theory and travel demand modelling to road safety and logistics and supply chain modelling, the work of the ISTTT is hallmarked in all its topics of interest by innovation, research and rigour in analytical treatment of real world transport and traffic problems. The ISTTT has been held in cities around the world about once every three years, starting in Detroit in 1959. Subsequent symposia have been held in London, New York, Karlsruhe, San Francisco (twice), Sydney, Kyoto, Toronto, Delft, Boston (Mass), Yokohama, Lyon and Jerusalem. No more than 35 papers are selected for presentation, following a rigorous two-stage selection and peer review process (of extended abstracts and full papers).The proceedings define the international state of the art in traffic and transport research at the time of the symposium. Amongst the topics covered in the book are: traffic flow theory, traffic management and traffic control; intelligent transport systems; analytical techniques for road safety; travel demand modelling, including dynamic traffic assignment, route control and congestion pricing; environmental impact analysis for transport systems; public transport planning, service design and operations; freight transport modelling; logistics and supply chain modelling; pedestrian and bicycle transport.